2008
DOI: 10.1097/wnr.0b013e3282f76151
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1 receptors are expressed in mouse and frog semicircular canal sensory epithelia

Abstract: Histamine-related drugs are commonly used in the treatment of vertigo and related vestibular disorders. Their site and mechanism of action, however, are still poorly understood. To increase our knowledge of the histaminergic system in the vestibular organs, we have investigated the expression of H1 and H3 histamine receptors in the frog and mouse semicircular canal sensory epithelia. Analysis was performed by mRNA reverse transcriptase-PCR, immunoblotting and immunocytochemistry experiments. Our data show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…at the afferent vestibular nerve, since H3 antagonists were still effective when the synapse was blocked by a high Mg 2+ /low Ca 2+ solution [ 11 ]. This hypothesis is consistent with the present results, and also with a recent study showing no evidence for H3 receptors expression by vestibular hair cells [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…at the afferent vestibular nerve, since H3 antagonists were still effective when the synapse was blocked by a high Mg 2+ /low Ca 2+ solution [ 11 ]. This hypothesis is consistent with the present results, and also with a recent study showing no evidence for H3 receptors expression by vestibular hair cells [ 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, experiments performed on amphibian semicircular canals have shown that H1 and H3 receptor ligands affect the sensory input recorded from the afferent vestibular neurons [ 9 - 11 ], indicating a possible peripheral site of action for these drugs. Consonant with the latter studies, we recently reported that H1 receptors are expressed in frog and mouse hair cells [ 12 ].…”
Section: Introductionmentioning
confidence: 90%
“…Studies using RT-PCR and immunoblotting and immunocytochemical experiments in frog and mouse semicircular canal sensory epithelia showed that both frog and mouse vestibular epithelia express H 1 receptors, although no clear evidence for H 3 receptor expression in hair cells was found [19]. However, RT-PCR analysis showed the presence of H 3 receptor mRNA in mouse vestibular ganglia, and H 3 protein expression was found in vestibular neurons characterized by large and round soma, which showed positive staining for calretinin and calbindin [153].…”
Section: Drugs With Effects On Neurotransmitters and Neuromodulator Rmentioning
confidence: 99%
“…However, the specific topic of histamine and its signaling in the cochlea or vestibular organs remains scarcely addressed in the literature. A few research teams have identified the expression of histamine receptors in the inner ear of mammals [38][39][40][41]. Additionally, in 2020, our group found mast cells in the inner ear of both rats and mice [42].…”
Section: Introductionmentioning
confidence: 86%